PEMANFAATAN BITTERN SEBAGAI KOAGULAN ALTERNATIF PENGOLAHAN LIMBAH CAIR DOMESTIK GAMPONG TIBANG KOTA BANDA ACEH - Husnul Khatimah; Rizna Rahmi; Teuku Muhammad Ashari (Lingkar : Journal of Environmental Engineering, 2022)
Domestic liquid waste contains high organic matter when it enters the body of water causing environmental pollution. Utilization of natural coagulants such as bittern can be used in the process of processing domestic liquid waste. This study was conducted to be able to know the effectiveness and optimum dose of bittern biocoagulants in lowering the levels of turbidity, TSS, COD and BOD in domestic wastewater. Based on the initial test results of domestic wastewater pH values of 7.2 turbidity, TSS, and COD of 70 NTU, 326 mg/L, and 716 mg/L and 19.02 mg/L. The results showed that there was an influence on the dose of bittern coagulants 0, 8, 16 and 24 ml/L with stirring times of 30 minutes and 60 minutes. The optimum dose of bittern coagulants in lowering pH, turbidity, TSS, COD and BOD at doses of 24 ml/L amounting to 8.0, 18 NTU, 94 mg/L, 121 mg/L and 9.39 mg/L. Effectiveness of bittern coagulants in domestic liquid waste treatment for pH and BOD levels is as expected because it meets established quality standards, while the parameters of turbidity, COD and BOD results are still passed the quality standards.